Mongolia as a Modern Sovereign Nation-State - Bedeski, Robert E (Mongolian Journal of International Affairs, 2011)
DOI: 10.5564/mjia.v0i13.10 Mongolian Journal of International Affairs No.13 2006 pp.77-87